Effect of Ellipse-Shaped Granular Bed on 2-Dimensional Brazil Nut Effect - SIBAQ UKHROWI ULWI - Nim:10212007, AHMAD
Granular material is a mixture of macroscopic particles in a massive amount. One of its unique phenomena is Brazil Nut Effect. Brazil nut effect phenomenon happens when the bigger sized particle called intruder, which at the bottom of the granular bed, rising to the top of granular bed when vibrated vertically. To study the effect of granular bed shape on brazil nut effect, we will conduct this experiment using ellipse-shaped granular beds. Testing of ellipse-shaped effect using 2-dimensional experiment, so that the trajectory of the intruder can be measured. The test will be conducted with variations of frequencies, ellipse’s aspect ratio, and intruder’s shape. From the experiment, ellipse-shaped granular bed shows that less time needed for the intruder to rise to the top of granular bed than using disk-shaped. The trajectory of the intruder in ellipse-shaped granular going up more consistent than in round-shaped granular.